2016
DOI: 10.1681/asn.2016030345
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Revascularization in Patients with CKD Stage 5D: Pragmatic Considerations

Abstract: Coronary revascularization decisions for patients with CKD stage 5D present a dilemma for clinicians because of high baseline risks of mortality and future cardiovascular events. This population differs from the general population regarding characteristics of coronary plaque composition and behavior, accuracy of noninvasive testing, and response to surgical and percutaneous revascularization, such that findings from the general population cannot be automatically extrapolated. However, this high-risk population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…While CABG was shown to be superior to PCI in patients with multivessel CAD and endstage renal disease regarding long-term survival, PCI was superior to CABG in short-term survival, stroke, and repeat revascularization [11]. However, data on the long-term performance of new-generation DES indicate no significant difference between PCI and CABG in patients with CKD [11][12][13][22][23][24]. Previous studies on revascularization have shown that patients with CKD after PCI and CABG are at increased risk of death and adverse events, correlating with the severity of renal insufficiency [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While CABG was shown to be superior to PCI in patients with multivessel CAD and endstage renal disease regarding long-term survival, PCI was superior to CABG in short-term survival, stroke, and repeat revascularization [11]. However, data on the long-term performance of new-generation DES indicate no significant difference between PCI and CABG in patients with CKD [11][12][13][22][23][24]. Previous studies on revascularization have shown that patients with CKD after PCI and CABG are at increased risk of death and adverse events, correlating with the severity of renal insufficiency [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Severe and diffuse CAD is prevalent in patients with CKD [5][6][7][8][9][10]. In those patients, revascularization options include coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) [11][12][13]. Adverse event rates following PCI and CABG were significantly higher in CKD patients when compared to patients with normal renal function [5][6][7][8][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patient did not have occlusive disease (i.e., stenosis $70%) that would normally warrant revascularization (6). The relevant considerations regarding revascularization include the fact that the degree of coronary stenosis does not predict future plaque rupture and that 30% of perioperative myocardial infarctions occur in areas supplied by arteries with nonocclusive plaque (7,8). In this patient, a large territory of myocardium would be at risk in the event of a myocardial infarction.…”
Section: Should the Patient Be Revascularized?mentioning
confidence: 99%